Development of adolescents' leisure interests and social involvement: perspectives and realities from youth and local stakeholders in Quebec. Issue 1 (2nd January 2016) - Roult, Romain; Royer, Chantal; Auger, Denis; Adjizian, Jean-Marc
Abstract : Many municipal stakeholders deplore the poor participation of adolescents in out-of-school activities while also acknowledging their lack of understanding about the latter's interests in terms of leisure. Therefore, this study is to further understand how adolescents develop their leisure expectations and their level of social involvement in their communities. For these purposes, 18 focus groups were conducted with 72 youth aged between 12 and 17 years old as well as with 26 local stakeholders. The findings show that the way these adolescents approach leisure is closely linked to personal convictions and motivations along with the search for pleasure. This study also shows evidence of a strong influence from the family and from peers in regard to how these youth assert their leisure interests and get involved in their communities. Finally, this study underlines the importance of fostering adolescents' participation by allowing them to get involved in programming and entertaining the recreational offer in their community.